The rise of the dragon : inward and outward investment in China in the reform period, 1978-2007 - Brown, Kerry, 1967-; Von Ruda, Ataullah Gabriel; ScienceDirect eBooks (Oxford : Chandos, 2008)
Chinese economic reform has been undertaken through a series of phased reforms. The goal of Chinese economic reform was to generate sufficient surplus value to finance the modernization of the mainland Chinese economy. This book provides an assessment of where investment stands today and it's likely future role in China. It reviews China's interaction with the rest of the world as the country advances towards superpower status. Provides and accessible study of both inward and outward investment - not found in other books on ChinaBased on clear case studies while the author worked as an Embassy commercial officer from 2000 to 2003 in China, and then as a consultant for Western companies, and Chinese companies, seeking to implement inward and outward investment plans.
Introduction: how to spend a trillion dollars -- an overview of the current status of China's foreign reserves, and its policy towards inward and outward investment, and why this is a critical issue for China's development, and its engagement with the rest of the world.; What the figures say. An overview of what the official and unofficial inward and outward investment figures over the last three decades say -- and what they conceal.; History: how investment started to figure in the Chinese economy after the years of closure under Mao. Why inward investment was important in the 1980s, when the reform process started, and where it first appeared (in the Special Economic Zones). What it's mixed fortunes were until the Tiananmen Square Event in 1989, and what changes this made to attracting inward investment policy on the Chinese government's side, and to those investing from outside. Why China started to encourage outward investment in the 1990s, and what the position is now.; What it looks like from the inside -- inward investment in China -- looking at the case studies from three areas -- UK inward investment in China, German inward investment, and US inward investment, taking clear case studies from each area, and looking at how they have been structured, what their strategic positioning has been, and what they show about the larger economic and political relationship between the respective countries and China; The other way round: China's emergence as an outward investor: looking at three aspects -- China as a purchaser of foreign companies (the case of Nanjing Auto and Rover); China as a strategic investor (China's investment in Hamburg, Germany, and Huawai in UK), and China as a raiser of capital (China's 47 companies listed on AIM in London). How does this relate to the emergence of the non-State sector in China in the last two decades? What is the current status of these investment?; The future: indications of China realizing its economy is over reliant on foreign direct investment.
Includes bibliographical references (pages 199-206) and index.
Print version record.
Elsevier
Keywords: Investments, Foreign -- China; Investments, Chinese -- Foreign countries; China -- Economic conditions -- 1976-2000.; China -- Foreign economic relations; BUSINESS & ECONOMICS -- Finance; Investition; Wirtschaftsentwicklung; China; Electronic books